Nursing education in New Zealand, 1883 to 1930 : the persistence of the Nightingale ethos : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Education at Massey University - Rodgers, Janice Ann (Massey University, 1985)
This thesis argues that the Nightingale ethos shaped the development and progress of nursing training in New Zealand during the years 1883 to 1930. The Nightingale ethos with its allegiance to the traditional belief in women's responsibility for nurturance, cleanliness and order, along with the truly 'feminine' traits of forbearance, endurance and obedience, paralleled the idealised vision of woman, mother and 'helpmeet'. That Florence Nightingale saw nursing as a natural extension of the role of female both advantaged and hindered nurse training. From a period of amateurism when every woman was a nurse, there developed a belief that nursing was women's work, an acceptable occupation for females. This same belief was used by administrators to provide an economically stringent hospital service, with the nursing service situated in hospitals, probationers providing the service while receiving a training. It is my contention that the Nightingale ethos was incompatible with advanced training for nurses. Even when nurse training was provided with the opportunity for a new direction-a university education - the pervasiveness of the Nightingale ethos prevented this. The training scheme for nurses remained within the hospital structure perpetuating the unwritten, unformulated belief that nurses' work was women's work.
Keywords: Nursing schools; New Zealand; Nursing; Study and teaching